The Relationship Between the Eleventh-Grade Students' Self-Confidence and Their Speaking Ability of SMA Ip Yakin C - Sabilar Rosyad (Syntax Corporation Indonesia, 2024)
This study aims to determine the relationship between confidence and speaking ability of grade XI students at SMA IP Yakin Cengkareng, West Jakarta. The research method used is a correlational method with instruments like confidence questionnaires and speaking tests. Data were collected from 30 students in grade XI science who were selected through the purposive sampling technique. The results showed that there was a significant relationship between students' confidence and speaking ability, with a correlation coefficient value of 0.850, which means that alternative hypotheses were accepted. These findings suggest that increased students' confidence can have a positive impact on their speaking skills in English.